The Influence of Principal Leadership and Non-Physical Work Environment on Teacher Performance at SMA Negeri 6 Semarang - Ardea Yoga Oktarya Gamma; Amin Yusuf; Dorojatun Prihandono (Universitas Negeri Semarang, 2025)
This study is motivated by the importance of teacher performance in education, and aims to analyze the influence of principal leadership and non-physical work environment on teacher performance at SMA Negeri 6 Semarang, both partially and simultaneously. The results of the study are expected to provide insight into improving teacher performance through a better managerial approach. The quantitative research method used is an ex post facto survey design. The sample consisted of 64 teachers selected through purposive sampling, and data were collected using a questionnaire. To analyze the influence of independent variables (principal leadership and non-physical work environment) on the dependent variable (teacher performance), multiple regression analysis was conducted through SPSS and JASP software. The findings showed that both independent variables had a significant effect on teacher performance at the location. Partially, both variables had a positive effect. The results of the simultaneous ANOVA test also confirmed that these two factors have a joint effect on teacher performance. The conclusion of the study is that principal leadership and non-physical work environment play an important role in improving teacher performance. Improving the quality of leadership and optimizing the work environment can contribute to enhancing teacher performance in planning, implementing, and evaluating learning. Therefore, it is important for all related parties to continue to pay attention to and develop these two factors to improve the quality of education in schools.